Morphology and anatomy of flowers and seeds of Lippia alba Morfología y anatomía de las flores y semillas de pronto alivio - Sánchez Manuel Salvador; Vallejo Cabrera Franco Alirio; Muñoz Aida (Acta Agronómica)
For description three accesions of L. alba from Llanos Orientales and Valle (Colombia) and Costa Rica (Central America) were used. The inflorescences are simples and racemoses. The flowers are small, sessiles, lilac color, disposed trought of the rachis, localizated in the axillas, coupled and apposited. The flowers in primary, secondary and tertiary branches present two white sepals, pubescents with 1.5 mm of length. There is a green bract covering the sepals with a length between 3.0 and 5.0 mm. An openned flower measures up to 7.0 mm and between 3.0 and 4.0 mm of wide.
They are gamopetalous, zygomorphic, pubescents, tubulars, bilabiates, with four petals, hypogynous, syncarpic gynaeceum with two carpels, upper ovary, white-green style, yellow - greenish stigma. The anthers measure 0.2 mm of length. The fruit is a diachene, with two small seeds, its fruit size is around 2.0 mm of length and 1.8 mm of wide; white, hard and dry coffee pericarp, pubescent and hard epicarp. The seed had a triangular form which measure between 0,8 mm in length and 0,3 mm wide.

Keywords: Lippia alba, Verbenaceae, floral biology, seeds. En la descripción se utilizaron tres accesiones de Lippia alba provenientes de Llanos Orientales y Valle (Colombia) y Costa Rica (Centro América).
Las inflorescencias son espigas racemosas simples, de flores sésiles, color lila pálido y dispuestas a lo largo del raquis, localizadas en las axilas, en pares y opuestas. Las flores dispuestas en ramas principales, secundarias y terciarias presentan dos sépalos blancos, pubescentes y miden 1.5 mm de longitud. Cubriendo cada par de sépalos hay una bráctea verde, ovada y posee una longitud entre 3 y 5 mm. Una flor abierta mide hasta 7.0 mm y entre 3 y 4 mm de ancho. Son gamopétalas, zigomorfas, pubescentes, tubulares, de color lila, bilabiadas, con cuatro pétalos, hipóginas, gineceo sincárpico y bicarpelar, ovario súpero, verde blanquecino, estilo blanquecino y estigma amarillo verdoso y forma capitada. Las anteras miden 0.2 mm de largo. El fruto es diaquenio, mide alrededor de 2 mm de largo y 1.8 mm de ancho, el pericarpio es blanco, duro y seco, el epicarpio es duro, café y pubescente. La semilla es triangular y mide entre 0.8 mm de largo y 0.3 mm de ancho.

Palabras claves: Lippia alba, Verbenaceae, biología floral, semillas.